2022
DOI: 10.1002/solr.202200176
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid‐Tuned Crystallization for Stable and Efficient Perovskite Solar Cells

Abstract: Organometal halide perovskites as the core of the next-generational photovoltaic technologies have attracted remarkable attention due to their advantages of low material cost, easy fabrication, and outstanding photovoltaic properties. [1] Significant efforts have been made to enhance the photovoltaic performance of perovskite solar cells (PSCs). [2] The power conversion efficiency (PCE) has been boosted to about 26%, [3] which is comparable to that of conventional photovoltaic technology based on crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Organic-inorganic halide perovskite solar cells (PSCs) have attracted great research interest due to their superb optoelectronic properties. [1][2][3][4][5][6][7] In the past decade, the record power conversion efficiency (PCE) of all-solid-state single-junction thin-film PSCs has jumped from 9.7% to 25.7%, mainly benefiting from the enormous compositional and interface engineering. [8][9][10][11][12][13][14] For PSCs achieving record PCE and stability, the perovskite layer was turned from the original MAPbI 3 -to FAPbI 3 -based compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic halide perovskite solar cells (PSCs) have attracted great research interest due to their superb optoelectronic properties. [1][2][3][4][5][6][7] In the past decade, the record power conversion efficiency (PCE) of all-solid-state single-junction thin-film PSCs has jumped from 9.7% to 25.7%, mainly benefiting from the enormous compositional and interface engineering. [8][9][10][11][12][13][14] For PSCs achieving record PCE and stability, the perovskite layer was turned from the original MAPbI 3 -to FAPbI 3 -based compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The IL BAAC was also employed as an additive to tune the crystallization of Cs 0.05 (FA x MA y ) 0.95 Pb(I x +0.05 Br y Cl y ) 3 perovskite films by Ran and coworkers. [ 15 ] It was found that the BAAc can react with PbI 2 by forming chelate bonds (C=O–Pb) and hydrogen bonds (N–H···I), retarding perovskite crystal growth. Therefore, the average grain size increased from about 476–620 nm, and the PCE elevated from 18.4% to 20.1%.…”
Section: Ionic Liquids As Additives For Perovskite Filmsmentioning
confidence: 99%
“…In addition to those mentioned above, many other functional groups have been introduced into ILs to improve the efficiency and stability of PSCs (Table 1), such as benzal groups (-CH 2 C 6 H 5 ), [7,36] vinyl groups (-CH=CH 2 ), [7,33,36] amide groups (-CONH 2 ), [37] and carboxyl groups (-COOH). [8,[11][12][13]15,19,38] In conclusion, to design an effective IL, first, an electron-rich chemical structure is necessary, such as imidazole rings, pyridine rings, and pyrrolidine rings, which can provide electrons to neutralize trap states. Second, the spatial hindrance effect should be considered.…”
Section: Influence Of Ionic Liquids Chemical Structure and Functional...mentioning
confidence: 99%
“…Their employment as layers between the different interfaces of the devices, especially between the perovskite and the hole transporting material (HTM), promotes the extraction of the charge carriers by creating an intermediate energy level between the charge transport layer and the perovskite. Their incorporation as solvents and inside the perovskite solution slows down the crystallization of the film as a result of their nonvolatile character, which helps the formation of larger, highly oriented, and almost defect-free crystals . While their hydrophobic character (hydrophobic alkyl chain) protects from the penetration of the humidity, ILs assemble periodic structures with halides, rendering the perovskite more stable by a strong chemical bonding and, in parallel, mitigating the trap-state density at the interfaces and grain boundaries. , Many groups have reported studies on how ILs passivate the perovskite layers and the interfacial reactions among them. …”
Section: Introductionmentioning
confidence: 99%